2009
DOI: 10.3402/rlt.v17i2.10871
|View full text |Cite
|
Sign up to set email alerts
|

Beyond podcasting: creative approaches to designing educational audio

Abstract: This paper discusses a university-wide pilot designed to encourage academics to creatively explore learner-centred applications for digital audio. Participation in the pilot was diverse in terms of technical competence, confidence and contextual requirements and there was little prior experience of working with digital audio. Many innovative approaches were taken to using audio in a blended context including student-generated vox pops, audio feedback models, audio conversations and task-setting. A podcast was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…This Finnish inter-university online course suggests that novel formative audio feedback practice, which was inspired by and followed the peer-review practices employed by scientific journals, was promising in promoting the emotional engagement of students and personal connectivity between students and instructors in a mobile learning setting. The study confirms earlier knowledge in that audio feedback was perceived personal (Dixon, 2015;Middleton, 2009;Parkes & Fletcher, 2014) and adds that this was experienced whether or not the students met with their instructor face-toface (cf. Woodcock, 2016).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This Finnish inter-university online course suggests that novel formative audio feedback practice, which was inspired by and followed the peer-review practices employed by scientific journals, was promising in promoting the emotional engagement of students and personal connectivity between students and instructors in a mobile learning setting. The study confirms earlier knowledge in that audio feedback was perceived personal (Dixon, 2015;Middleton, 2009;Parkes & Fletcher, 2014) and adds that this was experienced whether or not the students met with their instructor face-toface (cf. Woodcock, 2016).…”
Section: Discussionsupporting
confidence: 87%
“…Studies indicate that asynchronous instructor audio feedback has been positively received by students and that they prefer audio feedback to written feedback (Parkes & Fletcher, 2014). Middleton (2009) presented results from a university-wide pilot designed to encourage academic staff to implement digital audio, including audio feedback, in their teaching practices. Based on the pilot, he concluded that if teachers are offered enough timely technical support, audio materials can help add a social presence and connectivity between students and teachers (see also Parkes & Fletcher, 2014).…”
Section: Previous Research On Audio Instructor Feedbackmentioning
confidence: 99%
“…Jashapara and Tai (2011) argued that although people may have different levels of computer experience, innovativeness, and playfulness in e-learning settings, self-efficacy and anxiety play a crucial role in influencing their attitudes towards e-learning. Lack of technological expertise was revealed as the result to fear of working in e-learning environment (Middleton, 2009). Jashapara and Tai (2011) pointed on the critical role of training programs to alleviate computer anxiety.…”
Section: E-learningmentioning
confidence: 99%